Benefits of inclusive physical activity for people with Down syndrome: systematic review. - Silva-Ortiz, A.M.; Gamonales, J.M.; Gámez-Calvo, L.; Muñoz-Jiménez, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The aim of the work was to conduct a review of the literature related to physical activity as a medium of inclusion for people with Down syndrome. For references search, the following keywords were used as descriptors: Inclusion, Down Syndrome, and Physical Activity. The databases used were Web of Science and SCOPUS. To limit the search, five inclusion criteria were established: i) Mention at least some of the characteristics of people with Down Syndrome, ii) Use the Physical Activity iii) Only scientific articles were selected, iiii) complete text available, and iiiii) Be written in English. Twenty-one papers were selected, where the data of the included articles were extracted and synthesized. In conclusion, the documents address different research topics and have allowed to know the benefits of physical activity and the least investigated areas, as well as to know the main recommendations to improve the quality of life of people with Down syndrome.